Modulation of the Toll-like Receptor 3-Mediated Intestinal Immune Response by Water Kefir - Dentice Maidana, Stefania (2024)
Kefir has been associated with beneficial effects on its host’s health. The previous works examining the impact of kefir on the immune system focused on milk kefir or the exopolysaccharides and bacterial strains derived from it, while water kefir has not been evaluated. Furthermore, studies have focused on kefir’s ability to modulate immune system hemostasis and exert anti-inflammatory effects, while its specific action on antiviral immunity has not been investigated. Thus, the aim of this work was to examine the potential immunomodulatory effects of water kefir on the intestinal innate antiviral immunity mediated by Toll-like receptor-3 (TLR3). Adult BALB/c mice fed water kefir ad libitum, diluted 1:5, 1:10, or 1:20 in the drinking water, for 6 consecutive days. On day 7, the treated groups and the untreated control mice received an intraperitoneal injection of the TLR3 agonist poly(I:C). Two days after the TLR3 activation, the intestinal damage and the innate immune response were studied. The intraperitoneal administration of poly(I:C) induced inflammatory-mediated intestinal tissue damage, characterized by the upregulation of interferons (IFNs), pro-inflammatory mediators (TNF-α, IL-15, IL-6), and factors involved in epithelial destruction (RAE-1 and NKG2D). The histological analysis of small intestinal samples showed that mice receiving water kefir 1:5 exhibited reduced edema and a lower inflammatory cell infiltration. Kefir-treated mice had significantly lower levels of serum LDH, AST, and ALT as well as intestinal TNF-α, IL-15, IL-6, RAE-1, and NKG2D. This group also showed higher concentrations of intestinal IFN-β, IFN-γ, and IL-10. The treatment with 1:10 of water kefir reduced intestinal damage and modulated cytokines but its effect was significantly lower than the 1:5 treatment, while the water kefir 1:20 did not modify the parameters evaluated compared to control mice. The results indicate that water kefir exerts its immunomodulatory effects in a dose-dependent manner. The in vivo studies allow us to speculate that water kefir can induce two beneficial effects on the intestinal TLR3-mediated immune response: the enhancement of antiviral defenses and the protection against the inflammatory-mediated tissue damage. These protective effects of water kefir require further exploration to understand how water kefir, or its specific molecules/strains, can influence the immune response and to determine the extent of its protection against a real viral challenge.